PENGARUH ASIMETRI INFORMASI, KUALITAS AUDIT, KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN DI BEI PERIODE 2018-2022 - Nurhafifah, Nurhafifah; Sari, Nurshadrina Kartika; Ningsih, Wiwik Fitria (RISTANSI: Riset Akuntansi, 2024)
This study aims to analyze the effect of information asymmetry, audit quality, audit committee and firm size on earnings management. The object of this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample selection used a purposive sampling method, so that a total of 32 bank companies were obtained. The research method used is a quantitative approach to the method of analysis, namely multiple linear regression analysis with dummy variables. The results of this study indicate that (1) information asymmetry and audit quality have no effect on earnings management (2) audit committee and firm size have an effect on earnings management. Simultaneously, information asymmetry, audit quality, audit committee and firm size have an influence on earnings management.